Student-Parent Communication System - Arumugam, Siva kumaaran (IRC, 2015)
This FYP described about Student Parent Communication System hardware prototype that in charge in helping the school kids to communicate with the parents at home or office. By overall, SPCS is a helpful communication device that is built according to latest technology and generation Y parents prefertences.